Decentralized Trusted Computing Base for Blockchain Infrastructure Security - Hardjono, Thomas; Smith, Ned (Frontiers in Blockchain, 2019)
There is a growing interest today in blockchain technology as a possible foundation for the future global financial ecosystem. However, in order for this future financial ecosystem to be truly global, with a high degree of interoperability and stability, several challenges need to be addressed related to infrastructure security. One key aspect concerns the security and survivability of the systems that participate in the blockchain peer-to-peer networks. In this paper we discuss the notion of the decentralized trusted computing base as an extension of the TCB concept in trusted computing. We explore how a decentralized TCB can be useful to (i) harden individual nodes and systems in the blockchain infrastructure, and (ii) be the basis for secure group-oriented computations within the P2P network of nodes. We explore the application of the decentralized TCB for blockchain interoperability via blockchain gateways. Similar to border gateways in classical IP routing, blockchain gateways may provide several potential benefits in use-cases involving the transferal of virtual assets across different blockchain autonomous systems.